Pengaruh Mikoriza dan POC Urin Sapi terhadap Pertumbuhan Cabai Merah di Zona Iklim Kering E - Parlindungan Sitepu, David; Sihotang, Saipul (Universitas Medan Area, 2025)
Red chili pepper (Capsicum annuum L.) is a horticultural commodity with high economic value that is greatly influenced by agroclimatic conditions. In dry climate zone E (Oldeman classification), plant growth is often hampered due to water limitations and low soil fertility. This study aims to evaluate the effect of arbuscular mycorrhizal administration and liquid organic fertilizer (POC) of cow urine on the vegetative growth of red chili plants in dry climate zone E. The study was conducted using a factorial Random Group Design (RAK) with two factors: mycorrhizal dose (0, 35, 85, and 135 g/plant) and POC concentration of cow urine (0, 30, 35, and 40 ml/L), Each was repeated three times, making a total of 48 experimental units. The parameters observed included plant height, number of leaves, stem diameter, time of emergence and number of shoots. The results showed that the dose of mycorrhizal 135 g and the POC concentration of 40 ml/L gave the best results on almost all vegetative parameters. The interaction of the two also showed a significant influence on plant height and number of shoots. These findings support the application of bioagent-based eco-friendly technologies in sustainable farming systems on dry climates.